Kearifan Lokal sebagai Model Integratif Pengelolaan Hutan Berbasis Masyarakat - Faiza Libby Shabira Lubis; Muhammad Sarjan (Universitas Mataram, 2026)
Forest management in Indonesia continues to face deforestation, degradation, tenure conflicts, and centralized governance that insufficiently reflects the socio-ecological characteristics of indigenous communities. This study aims to identify forest management principles embedded in local wisdom systems and examine their potential as an integrative model for community-based forest management. A qualitative literature review was conducted by synthesizing studies on local wisdom, Community-Based Forest Management, and adaptive co-management. The findings show that Tanah Ulayat, Rimbo Larangan, Tane’ Ulen, Sasi, Leuweung Larangan, and Awig-awig, despite emerging from different cultural contexts, share similar principles: territorial recognition, regulated resource use, customary institutional strengthening, social monitoring, and community participation. The synthesis produces an integrative model linking indigenous rights, traditional ecological knowledge, local institutions, and state regulatory support. This model offers a conceptual basis for adaptive, participatory, contextual, and sustainable forest governance, while requiring further empirical testing across Indonesia’s diverse socio-ecological landscapes and varied policy implementation settings.